2, 4-D Dichlorophenoxyacetic Acid Poisoning; Case Report and Literature Review - Sujata Hiran; Sunil Kumar (Asia Pacific Journal of Medical Toxicology, 2017)
Background: 2, 4-dichlorophenoxyacetic acid, (2, 4-D) is a selective herbicide available as the acids, esters and several salts which vary in their chemical properties, environmental behaviour, and to a lesser extent toxicity. The salt and ester forms are derivatives of the parent acid. It is widely used as a weed killer. The 2, 4-D dimethylamine is one of the salts of this group. Case Presentation: We report a case of ingestion of 2, 4-D herbicide intentionally. The patient had presented in a local hospital but transferred to our hospital in a state of deep coma. CT scan head showed diffuse cerebral oedema. The patient recovered completely after treatment with forced alkaline diuresis. Discussion: Anticholinesterase compounds are the most commonly used insecticide and the commonest compound used as poison in India. This case report emphasizes that not all poisonings are caused by anticholinesterase compounds. The initial clinical manifestations of 2, 4-dichlorophenoxyacetic acid (2, 4-D) poisoning are very similar to alcohol, sedative drugs, or aromatic chlorinated hydrocarbons making it even more difficult for the treating physician to suspect poisoning due to these compounds. It is thus important to identify the correct compound for proper management. Prompt diagnosis and correct treatment can save the life of a patient. The poisoning is also sometimes confused with poisoning due to anticholinesterase compound. Conclusion: 2, 4-D is a poison which carries a high mortality. Prolonged coma, metabolic complications, skeletal muscle injury and myotonia are some of the complications of 2, 4-D. Forced alkaline diuresis resulted in saving our patient which otherwise had poor prognosis.